Crystallographic orientation-dependent magnetic properties of a PrCo5 permanent magnet prepared by hot deformation. Issue 15 (8th March 2016) - Zhang, Dongtao; Yuan, Xiaokun; Yue, Ming; Zhou, Deshi; Zhu, Jie; Gao, Xuexu
Abstract : The preferential distributions of the habit planes at different locations in the PrCo5 bulk magnet (left center, middle sub-center, right edge) are different and correspond to different local magnetic properties. Abstract : We report a magnetically-anisotropic PrCo5 permanent bulk magnet, prepared by a hot deformation method, with crystallographic orientation-dependent magnetic properties. Although the PrCo5 crystals strongly favor the {0001} orientation texture, the crystallographic orientation textures of PrCo5 crystallites differ at various radial locations. From the bulk center to the edge, the c -axis orientation texture decreases from 5.4 MRD to 4.1 MRD, whereas the remanence decreases from 8.93 kGs to 7.58 kGs and the coercivity increases from 4.34 kOe to 6.56 kOe. This paper also reports the alteration of boundary plane orientation textures, resulting from the corresponding energy anisotropy at different locations, and suggests that the development of grain boundaries with lower boundary energies has a significant impact on the magnetic properties with regard to remanence and energy density. The current work therefore proposes an elegant approach to attain desired magnetic properties in PrCo5 magnets by fine-tuning the crystallographic orientation.